Systematics and phylogeography of the large land snail Powelliphanta : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Zoology, Massey University, New Zealand - Walker, Kathleen Joy (Massey University, 2018)
Without a generally accepted name, a species is less likely to receive conservation effort. For the large, colourful and carnivorous land snails in the New Zealand genus Powelliphanta, doubts about the validity of the existing morphologically-based nomenclature, and the absence of taxonomic assessment for many late-discovered taxa, have been hindering conservation efforts. Powelliphanta have been in decline due to continuing loss of habitat and a suite of predators recently introduced to New Zealand, but scarce conservation resources are targeted to formally described taxa. The aim of this study was to review and if appropriate revise the taxonomy of the genus to remove any taxonomic impediment to conservation action. Like other Pacific Ocean archipelagos, the fauna and flora of New Zealand is characterised by a small number of families with extensive radiations. Understanding of relationships is often hindered by the recency of lineage separations and requires multiple lines of evidence. Allozymes and mitochondrial sequences were used to identify genotypic clusters in Powelliphanta and to assess the relationship with presumed sister taxa Victaphanta. A matrix of morphological characters was assembled for multivariate analysis. These characters included for the first time in Powelliphanta, features of the soft body and Fourier coefficients describing subtle shape differences. Intraspecific variation within one of the species, P. lignaria, received detailed distributional, morphological and genetic evaluation to investigate the use of subspecies in the genus. Powelliphanta fiordlandica was found to be a sister taxon to all other Powelliphanta, with a deep genetic divergence and differences in morphology indicating it should be placed within its own monotypic genus. Allozymes, mtDNA and morphology all identified similar clusters, many of which equated to the already described taxa and to taxa which had been tag-named but remained undescribed. Shell colour, pattern and size, which show environmental plasticity in some molluscs, were found in Powelliphanta to be genetically-based and shape also proved informative. The described subspecies of Powelliphanta lignaria were found to be morphologically diagnosable, largely allopatric, and with gene flow limited to the extent that the integrity of each subspecies has been maintained. A recently discovered and critically threatened species was described as Powelliphanta augusta, and a new classification for the genus comprising 20 species and 59 subspecies (including the existing P. lignaria subspecies) was proposed.
Keywords: Powelliphanta; Classification; Geographical distribution; Snails; New Zealand; 060411 Population, Ecological and Evolutionary Genetics